2019
DOI: 10.3390/nu11092052
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Dietary Pattern Predicts Dyslipidemia and Anemia in Middle-Aged and Older Taiwanese Adults with Declined Kidney Function: A Cross-Sectional Population Study from 2008 to 2010

Abstract: Dyslipidemia, anemia, and inflammation are associated with declined kidney function. This study investigated the association of inflammatory dietary pattern with dyslipidemia, anemia, and kidney function biomarkers among middle-aged and older Taiwanese adults with declined kidney function. Biochemical data and food frequency questionnaire were obtained from 41,128 participants with estimated glomerular filtration rate (eGFR) <90 mL/min/1.73 m2 and positive urinary protein. Inflammatory dietary pattern was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, only men who had greater consumption of a prudent dietary pattern decreased the risk of different indices of adiposity. The western dietary pattern in this study is comparable to the western pattern reported by Muga et al [28] and Syauqy et al [29], which included high intakes of processed food, meat, high-fat products, sauces, sweets, and sugary beverages. The EPIC-PANACEA (European Prospective Investigation into Cancer and Nutrition-Physical Activity, Nutrition, Alcohol, Cessation of Smoking, Eating Out of Home, and Obesity) study had similar findings that excess consumption of red meat, poultry, and processed meat might contribute to an increased risk of obesity [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, only men who had greater consumption of a prudent dietary pattern decreased the risk of different indices of adiposity. The western dietary pattern in this study is comparable to the western pattern reported by Muga et al [28] and Syauqy et al [29], which included high intakes of processed food, meat, high-fat products, sauces, sweets, and sugary beverages. The EPIC-PANACEA (European Prospective Investigation into Cancer and Nutrition-Physical Activity, Nutrition, Alcohol, Cessation of Smoking, Eating Out of Home, and Obesity) study had similar findings that excess consumption of red meat, poultry, and processed meat might contribute to an increased risk of obesity [35].…”
Section: Discussionsupporting
confidence: 88%
“…The food group was considered in the dietary pattern with a higher factor loading value if the factor loadings of the food group were ≥ 0.30 in more than one dietary pattern. The factor score for each dietary pattern was calculated by using the sum of food consumption scores divided by factor loadings, and then each dietary pattern was further divided into quartiles [29].…”
Section: Methodsmentioning
confidence: 99%
“…The Western dietary pattern has been shown to have inflammatory effects, according to the previous study by Kurniawan et al [14]. The inflammatory dietary pattern, with high intakes of eggs, meat, preserved/processed foods, and sugary beverages, but low intakes of grains, vegetables, and fruits, was associated with an increased risk of anemia by 28-47% in middle-aged and older Taiwanese adults with impaired kidney function [14]. High adherence to the Western dietary pattern, and the status of being overweight or obese, could be associated with low-grade inflammation, which leads to a higher incidence of anemia.…”
Section: Dietary Pattern and Anemiamentioning
confidence: 86%
“…Additionally, a previous study performed with Thai girls aged 13-15 years reported that 85.5% students consumed dietary iron at <67% of the Recommended Daily Allowance, and most students ate fewer green vegetables and fruits with their meal and drank more sweetened juice [44]. The Western dietary pattern has been shown to have inflammatory effects, according to the previous study by Kurniawan et al [14]. The inflammatory dietary pattern, with high intakes of eggs, meat, preserved/processed foods, and sugary beverages, but low intakes of grains, vegetables, and fruits, was associated with an increased risk of anemia by 28-47% in middle-aged and older Taiwanese adults with impaired kidney function [14].…”
Section: Dietary Pattern and Anemiamentioning
confidence: 98%
“…Chun et al suggested that high levels of sugar-sweetened beverage consumption were associated with a higher prevalence and extent of coronary artery calcification [37]. Kurniawan et al also concluded that sugar-sweetened beverages were associated with an increased risk of dyslipidemia [38]. Individuals who drank sugar-sweetened beverages experienced a better sensory rewarding feel.…”
Section: Discussionmentioning
confidence: 99%